Gluteal fibrosis, post-injection paralysis, and related injection practices in Uganda: a qualitative analysis - Kristin Alves; Christine L. Godwin; Angela Chen; Daniella Akellot; Jeffrey N. Katz; Coleen S. Sabatini (BMC, 2018)
Abstract Background Iatrogenic injection injury is a major cause of disability in Ugandan children. Two injuries thought to result from injection of medications into the gluteal region include post-injection paralysis (PIP) and gluteal fibrosis (GF). This study aimed to describe perceptions of local health care workers regarding risk factors, particularly injections, for development of GF and PIP. Specifically, we examine the role of injection practices in the development of these injuries by interviewing a diverse cohort of individuals working in the health sector. Methods We conducted a qualitative study in the Kumi and Wakiso Districts of Uganda in November 2017, utilizing 68 key informant interviews with individuals working in healthcare related fields. Interviews were structured utilizing a moderator guide focusing on injection practices, gluteal fibrosis and post-injection paralysis. Results We identified six themes regarding perceptions of the cause of GF and PIP and organized these themes into a theoretical framework. There was a consensus among the individuals working in healthcare that inadequacies of the health care delivery system may lead to inappropriate intramuscular injection practices, which are presumed to contribute to the development of GF and PIP. Poor access to medications and qualified personnel has led to the proliferation of private clinics, which are often staffed by under-trained practitioners. Misaligned economic incentives and a lack of training may also motivate practitioners to administer frequent intramuscular injections, which cost more than oral medications. A lack of regulatory enforcement enables these practices to persist. However, due to limited community awareness, patients often perceive these practitioners as appropriately trained, and the patients frequently prefer injections over alternative treatment modalities. Conclusion This qualitative study suggests that inappropriate intramuscular injections, may arise from problems in the health care delivery system. To prevent the disability of GF and PIP, it is important to not only address the intramuscular injections practices in Uganda, but also to examine upstream deficits in access, education, and policy enforcement.